2020
DOI: 10.1111/and.13728
|View full text |Cite
|
Sign up to set email alerts
|

CAG Repeats in the androgen receptor gene is associated with oligozoospermia and teratozoospermia in infertile men in Jordan

Abstract: CAG trinucleotide repeats are coded for the polyglutamine tract in the N-terminal of the androgen receptor (AR) gene which varies in normal individuals from 6 to 36 residues. In this study, we inspected the impact of the CAG repeats on the spermatogenic defects by measuring the size of AR-CAG repeats length in a cohort of 260infertile and 169 fertile Jordanian men. The infertile group included three subgroups of a zoospermic, oligozoospermic and teratozoospermia men. The CAG allele size was determined by direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The distinct result of that study might be attributed to a relatively small study population (n = 47 infertile men and n = 32 controls) compared to our study which included 113 fertile and 312 infertile subjects. Similarly, a recent study has indicated no association between CAG repeat expansion and NOA in Jordanian men (Al Zoubi et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…The distinct result of that study might be attributed to a relatively small study population (n = 47 infertile men and n = 32 controls) compared to our study which included 113 fertile and 312 infertile subjects. Similarly, a recent study has indicated no association between CAG repeat expansion and NOA in Jordanian men (Al Zoubi et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…The most frequent CAG repetition (21) was reported in (55%) of fertile men. From our research, it is intriguing to discover different repeat sizes' distribution (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in both case and control participants. Almost the same (64%).…”
Section: Frequency Of Cag Expansion Among Case and Control Groupsmentioning
confidence: 84%
“…To determine if the categorical variables' distributions varied from one another, we used the Chi-square test. Among fertile and infertile males, the prevalence of CAG expansion in the Current research on CAG expansion found in the AR gene of infertile men, ranging from (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) repeats, which the mean CAG repeat was (21.3 ±0.16). The CAG repetition number that was seen the most frequently was 25 (16.7%).…”
Section: Frequency Of Cag Expansion Among Case and Control Groupsmentioning
confidence: 99%
“…Mitochondrial mutations are very common etiological pathogenic factors in energy-demanding organs such as muscles and the nervous system and are related to musculoskeletal and neurodegenerative disorders [ 4 ]. In addition, genetic alteration in the mtDNA may have significant effects on normal spermatogenesis and subsequently on fertilization [ 5 , 6 ]. Several reports have shown that mitochondrial dysfunction could lead to complete or partial spermatogenesis arrest and be an important causative factor in male infertility [ 7 ].…”
Section: Introductionmentioning
confidence: 99%